COMPACTION CHARACTERISTICS AND PHYSICAL PROPERTIES OF COMPACTED CLAY IN INDONESIA CONTROLLED BY THE DEGREE OF SATURATION - Oktoviana NIM: 25016019, Shara
The conventional fill compaction process usually controls the value of dry density (d) and water content () determined by laboratory compaction tests using a certain compaction energy level. As time goes by, required d value has been becoming higher for more satisfactory performance of soil structure. Therefore, very difficult to accurately estimate compaction energy level, referring to (d max) and water content (opt) in the field are usually unknown. The optimum degree of saturation (Sr opt) defined as Sr when d max is obtained for a given compaction energy level. Moreover, dd max vs Sr - Sr opt relation indicates an independent compaction energy level and soil type. To show a typical trendline of shear strength in clay, UCS test and Triaxial UU test are done in laboratory. Based on this research, the degree of saturation has been specified become an alternative way to control the soil density, using d enough value to achieve the physical properties required in design.